PsycEXTRA Dataset 2014
DOI: 10.1037/e562182014-001
|View full text |Cite
|
Sign up to set email alerts
|

Trauma, Symptomology, and Meaning in Life: A Comparison Between Clinical Samples and Healthy Controls

Abstract: TRAUMA, SYMPTOMOLOGY, AND MEANING IN LIFE: A COMPARISON BETWEEN CLINICAL SAMPLES AND HEALTHY CONTROLSResearch has shown that people who report living meaningful lives are better able to cope with trauma, integrate the past, present, and future into a guiding narrative, and report higher levels of self-esteem and life-satisfaction (Baumeister et al., 2013). Most research to date has examined meaning in life among psychologically healthy individuals, with a very limited number of studies examining meaning in lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…For example, one study by Appel et al [ 12 ] showed that the presence attenuated the relations between goal violation and post-traumatic stress (PTS) symptoms ( b = −0.17, p < 0.001), and between religious/spirituality struggles and PTS symptoms ( b = 0.18, p = 0.015). Similarly, other studies showed the mitigating effects of meaning in life on the links between hopelessness and suicide risk, between eating attitude and suicide ideation, and between eating attitude and hopelessness [ 13 , 14 ], although null moderating effects have also been reported [ 15 ].…”
Section: Introductionmentioning
confidence: 81%
“…For example, one study by Appel et al [ 12 ] showed that the presence attenuated the relations between goal violation and post-traumatic stress (PTS) symptoms ( b = −0.17, p < 0.001), and between religious/spirituality struggles and PTS symptoms ( b = 0.18, p = 0.015). Similarly, other studies showed the mitigating effects of meaning in life on the links between hopelessness and suicide risk, between eating attitude and suicide ideation, and between eating attitude and hopelessness [ 13 , 14 ], although null moderating effects have also been reported [ 15 ].…”
Section: Introductionmentioning
confidence: 81%